Pengembangan Modul Menulis Sastra Lama Berbasis Photo Story Untuk Siswa SMP - Ribut Wibowo; Mulyanto Widodo; Edi Suyanto (Universitas Lampung, 2020)
The problem in this research is related to the development of old story writing modules based on photo stories. The research objective is to produce a module product and describe the feasibility of the module